Two new species of Encyrtidae (Hymenoptera, Chalcidoidea) from the eastern Pamir Plateau, with four new records from China - Ouyan Xi; Shuli Zhang; Hongying Hu (ZooKeys)
Based on surveys of the superfamily Chalcidoidea (Hymenoptera) in the eastern part of Pamir Plateau from 2021 to 2023, 1770 specimens of Encyrtidae belonging to 21 species in 15 genera are identified and catalogued. Two new species, Acerophagus albuscorpus Xi & Hu, sp. nov. and Pseudectroma stemmatosteres Zhang & Hu, sp. nov., are described and illustrated. Four species, Ericydnus novosibiricus Sugonjaev & Gavrilyuk, 2012, Copidosoma charon Guerrieri & Noyes, 2005, Aphycus slavai Myartseva, 1981, and Trichomasthus marsus (Walker, 1837), are newly recorded from China, and their diagnoses and illustrations are provided.